(untitled) - 1964-; OConnor, Kevin J.; 1948-; Hyde, Jonathan; 1962-; Hannah, John; Weisz, Rachel; 1968-; Fraser, Brendan; 1971- (Universal City, CA, 2001)
As punishment for killing Pharaoh Seti and sleeping with his mistress, Egyptian priest Imhotep was mummified alive and cursed. But in 1923 he is inadvertently resurrected by treasure hunters and must be stopped before he can wreak his final vengeance on the world.
Keywords: Mummies; Drama; Video recordings for the hearing impaired; Feature films